Achieving Sustainability in Capture Fishing Industry Based on the Regional Characteristics - Batubara, Siti Chairiyah; Maarif, Muhamad Syamsul; Marimin, Marimin; Irianto, Hari Eko (International Journal of Supply Chain Management, 2016)
The prospect of the fishery sector becomes one of strategic economic activities, in which the government implements fisheries industrialization as a strategy to enhance added values of fishery production. The fishing industry is unique since it exploits fish as the main raw material naturally available and accessible by humans. Moreover, the capture fishing industry is relatively a high cost economy. This study was aimed at designing the regional-based institutional and network models of the fishing industry in order to achieve the sustainable fishing industry in Maluku province. The research employed Soft System Methodology to obtain an ideal model for the management of the sustainable capture fishing industry. Structure identification in designing the institutional model for a supply chain system of the sustainable fishing industry was carried out using the Interpretative Structural Modelling (ISM). Meanwhile, TOPSIS was involved in establishing a model for the fishing industry. The results show the institution that would be developed was a financial institution (cooperative) that would be managed and run by fishermen. The capture fishing industrial network in Maluku province was built by actualizing PPN Ambon as a main server in the route of PPI Masarette – PPI Eri – PPN Ambon. While Amahai would act as a main server for the route of PPN Tual – PPI Amahai and PPI East Tahme – PPI Amahai.